Commentary Imagine There's No DRM...I Wonder if You Can [NEWS]. - Perry, T.S (IEEE spectrum)
Digital rights management, the group of technologies that control copying and use of digital media downloads and disks, has infuriated consumers since its inception in the mid-1990s. Consumer advocacy groups rallied against it, arguing that locking digital content prevented not only illegal uses but legal ones as well. But the record and movie industries lobbied hard for enforcement of these locks, and in 1998 won the passage of the Digital Millennium Copyright Act, which made simply breaking one of these locks illegal, even if no copyright violation followed. The industries have taken the position that protection of artists' intellectual property is vital to their creative efforts. The initiatives are also good for consumer electronics companies, which will be able to sell new products to enable consumers to move that DRM-free music around. And there may even be benefits for recording artists, though the net impact of a DRM-free world on the fate of the record companies is less clear.